PERFORMANCE EVALUATION OF PROVITAMIN A MAIZE (Zea mays L.) HYBRIDS FOR YIELD AND OTHER AGRONOMIC TRAITS IN SOUTH-WEST NIGERIA - AKINTUNDE, ADEWOLE (Journal of Agricultural Sciences (Belgrade), 2024)
Maize is a major crop and staple food cultivated and consumed famers in Nigeria. The main nutritional components of maize kernel are carbohydrate, protein, fat, and several micronutrients, all of which are essential for human health. However, typical maize endosperm lacks sufficient amount of the nutritional precursor of vitamin to provide the body’s needed daily intake of protein and vital micronutrients. To attain food security and prevent malnutrition, it is necessary to cultivate stable, high-yielding pro-vitamin A maize hybrids that are appealing to rural people who suffer the most from ’hidden hunger.’ The purpose of this study was to evaluate the agronomic performance and yield of newly produced maize hybrids over a two-year period at two different sites. Twenty-two improved maize hybrids, two commercial hybrids, and a local check were assessed over two years in Ikorodu and Osogbo, Nigeria. Grain yields of hybrids varied from 3.33 t/ha (Ife-hybrid 3) to 5.69 t/ha (LY1409-61) across the years, with a mean of 4.03 t/ha. With the exception of Ife hybrid 3 (3.33 t/ha), all of the hybrids out-yielded the local check (3.92 t/ha), and four hybrids achieved grain yields of more over 5 t/ha across the two years. The distribution of precipitation in the two years in which the hybrids were examined (2019 and 2020) changed substantially. Because to the larger amount and distribution of precipitation in 2019, grain yields were much higher than in 2020, particularly throughout the flowering and grain filling stages of the maize life cycle, notably from July to October. The consistent performance of LY1409-61, AS1802-15, and LY1409-21 across years of assessment with varying weather circumstances suggests that the hybrids have the capacity to adapt to agro-ecology. The adoption of these maize hybrids by farmers would increase maize output and prevent malnutrition in rural parts of South-west Nigeria.